Factor V Enhances the Cofactor Function of Protein S in the APC-Mediated Inactivation of Factor VIII: Influence of the Factor VR506Q Mutation - Váradi, K; Rosing, J; Tans, G; Pabinger, I; Keil, B; Schwarz, H P (Thrombosis and Haemostasis, 1996)
Factor V and protein S are cofactors of activated protein C (APC) which accelerate APC-mediated factor VIII inactivation. The effects of factor V and protein S were quantitated in a reaction system in which plasma factor VIII was inactivated by APC and the loss of factor VIII activity was monitored in a factor X-activating system in which a chro-mogenic substrate was used to probe factor Xa formation. Factor V increased the rate of APC-mediated factor VIII inactivation in a dose-dependent manner in representative plasma samples with protein S or factor V deficiency, abnormal factor V (heterozygous or homozygous for factor VR506Q), or a combination of heterozygous protein S deficiency and heterozygous factor VR506Q. This effect was much less pronounced in the plasma samples with a decreased protein S level, but the impaired response in these plasmas was corrected by addition of protein S, indicating that both factor V and protein S are required for optimal inactivation of factor VIII by APC. The effects of factor V and protein S were also studied in a reaction system with purified proteins. APC-catalysed factor VIII inactivation was enhanced 3.7-fold in the presence of 1.1 nM factor V and 1.5-fold in the presence of 2.4 nM protein S. When both 1.1 nM factor V and 2.4 nM protein were present the rate enhancement was 11-fold. Factor V is a more potent cofactor than protein S, as can be concluded from the fact that 0.04 nM factor V gave the same stimulation as 2.4 nM protein S. Protein S lost its cofactor function after complexation with C4b binding protein, which indicates that it is free protein S that acts as a cofactor. To investigate the effect of the R506Q mutation in factor V on APC-mediated factor VIII inactivation, factor V was purified from the plasma of patients homozygous for factor VR506Q. In the absence of protein S, factor VR506Q did not enhance factor VIII inactivation by APC, but in the presence of 2.4 nM protein S a slight enhancement was observed. The APC cofactor activity of factor V was lost when factor V was activated with thrombin or with the factor V activator from Russell’s viper venom. These data indicate that optimal inactivation of factor VIII by APC requires the presence of an intact factor V molecule and free protein S.